2010
DOI: 10.1007/s11516-010-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

Promising effects of an intervention: Young children’s literacy gains and changes in their home literacy activities from a bilingual family literacy program in Canada

Abstract: The goal of this paper was to examine promising effects of a bilingual family literacy program: to track the changes of families' literacy activities through a bilingual family literacy intervention, and to examine the children literacy gains in both Chinese and English across socioeconomic sub-groups. The intervention was an eight-week, two hours per week, literacy program in three Chinese communities in Toronto. Parents, with their children, participated in the program. The extremely high attendance rate pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Although we can conclude that findings in the present study are consistent with theory on development from a bioecological perspective (Bronfenbrenner & Morris, 2006) and with previous FLP research documenting large vocabulary gains for ELLs (Roberts, 2008;Zhang et al, 2010), we wondered about the differences between our study and others relative to the function of initial vocabulary size. Recall that we found that children with very low English vocabulary knowledge achieved significantly larger gains than children with more English vocabulary knowledge contrasts with evidence from other studies; van Steensel et al (2011) and Roberts (2008) found that vocabulary gains associated with family literacy interventions did not differ as a function of initial vocabulary size.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Although we can conclude that findings in the present study are consistent with theory on development from a bioecological perspective (Bronfenbrenner & Morris, 2006) and with previous FLP research documenting large vocabulary gains for ELLs (Roberts, 2008;Zhang et al, 2010), we wondered about the differences between our study and others relative to the function of initial vocabulary size. Recall that we found that children with very low English vocabulary knowledge achieved significantly larger gains than children with more English vocabulary knowledge contrasts with evidence from other studies; van Steensel et al (2011) and Roberts (2008) found that vocabulary gains associated with family literacy interventions did not differ as a function of initial vocabulary size.…”
Section: Discussionsupporting
confidence: 49%
“…FLPs are grounded in the assumption that parents play an integral role in their children’s academic achievement and that children’s homes are a key context for supporting literacy and language development (Edwards & Turner, 2009). Although FLPs vary widely in program goals and features (e.g., parent training focused on school-based goals vs. authentic, home-based literacy events), learning contexts (home vs. at school), and family demographics (e.g., SES and language background), evidence documents positive effects of FLPs on parent/child home literacy practices (Brooks, Gorman, Harman, Hutchison, & Wilkin, 1996; Neuman & Gallagher, 1994; Paratore, 1993; Purcell-Gates et al, 2012; Rodríguez-Brown, 2004; Zhang, Pelletier, & Doyle, 2010). Moreover, evidence consistently demonstrates positive effects on children’s literacy outcomes (Anderson, Purcell-Gates, Jang, & Gagné, 2010; Brooks et al, 1996; Glynn, 1996; Hirst, Hannon, & Nutbrown, 2010; Jordan, Snow, & Porche, 2000; Páez, Bock, & Pizzo, 2011; Paratore et al, 2011; Rodríguez-Brown, 2004; Sénéchal & Young, 2008; van Steensel et al, 2011) and language outcomes (Anderson et al, 2010; Brooks et al, 1996; Jordan et al, 2000; Neuman & Gallagher, 1994; Páez et al, 2011; Paratore et al, 2011; Rodríguez-Brown, 2004; van Steensel et al, 2011; Zhang et al, 2010).…”
Section: Can Flps Moderate the Vocabulary Gap?mentioning
confidence: 99%
“…Other programs, also with small sample sizes, showed mixed results. Zhang, Pelletier & Doyle (2010) assessed the effects of a parental literacy program created for Chinese parents in Canada, including separate training for parents in Chinese and for their children in Chinese and English. Although the children showed immediate gains in expressive vocabulary on standardized measures, in both Chinese and English, there were no further statistically significant gains six months later, and children of more highly educated mothers showed more gains than children of less educated mothers.…”
Section: Resultsmentioning
confidence: 99%
“…Hope concluded that the programme helped to strengthen the relationships between school staff and parents. Zhang et al (2010) described a Chinese family literacy programme in a large urban centre in Canada. Although the print materials (e.g.…”
Section: Related Literaturementioning
confidence: 99%
“…Through the use of bilingual books (Hirst et al, 2010;Hope, 2011), the provision of instruction in the first language of the participants (Iddings, 2009;Zhang et al, 2010) and the incorporation of cultural practices into the curriculum (Iddings, 2009;Hirst et al, 2010), these programmes have successfully impacted children's language and literacy skills and the parents' ability to support children's literacy development at home.…”
Section: Related Literaturementioning
confidence: 99%